2010 11th International Symposium on Quality Electronic Design (ISQED) 2010
DOI: 10.1109/isqed.2010.5450442
|View full text |Cite
|
Sign up to set email alerts
|

Variation-aware speed binning of multi-core processors

Abstract: Abstract-Number of cores per multi-core processor die, as well as variation between the maximum operating frequency of individual cores, is rapidly increasing. This makes performance binning of multi-core processors a non-trivial task. In this paper, we study, for the first time, multi-core binning metrics and strategies to evaluate them efficiently. We discuss two multi-core binning metrics with high correlation to processor throughput for different types of workloads and different process variation scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…Furthermore, with the emergence of multi-core technology, intra-die variation has also become an issue. To minimize the overheads of guardbanding, recent efforts have shown that exploiting the inherent variation in devices [6], [7] yields significant improvements in overall system performance.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, with the emergence of multi-core technology, intra-die variation has also become an issue. To minimize the overheads of guardbanding, recent efforts have shown that exploiting the inherent variation in devices [6], [7] yields significant improvements in overall system performance.…”
Section: Introductionmentioning
confidence: 99%
“…There are a few strategies that are commonly adopted to combat the process variation problems. For example, performance (or speed) binning approach, which intends to pack processors into different classes based on their maximum operating frequencies, is a common method for profit maximization in the presence of frequency variation [37,140]. Performance binning is good for single core chips, however, it cannot capture the characteristic of a multi-core system.…”
Section: Uncertainty In Computing Infrastructuresmentioning
confidence: 99%
“…For example, performance/speed binning technique has been widely used to cluster chips with similar performance (e.g., frequency, leakage power) [141,122]. However, this approach didn't consider within-die variation.…”
Section: Related Work On Process Variationmentioning
confidence: 99%
See 2 more Smart Citations